Study and characterization of Sterculia foetida (Java olive) activated carbon black Filled composite materials - Srinivasa Rao Pedada; Srinivas Rao Golagani; Manoj Kumar Regulagadda; Anitha Kumari Mosya (Results in Chemistry)
High surface area activated carbon has been prepared from Sterculia Foetida by chemical activation with ortho-phosphoric acid at various temperatures (500–800 °C),weight ratios of ortho-phosphoric acid to sterculia foetida (P/L = 0.5–2.25) and impregnation times (1–48 h).as an activating agent were studied. Activated carbons with well-developed pore sizes were produced at activation temperatures of 500 and 800 °C. The BET surface areas and total pore volumes of the carbons produced at these temperatures are in the range of 1876–2678 m2/g and 1.49–1.62 cm3/g, respectively. Pore properties of the carbons including the BET surface area, pore volume, pore size distribution, and pore diameter were characterized from N2 isotherms The Fourier-infrared spectroscopy analysis of the prepared activated carbon has abundant functional groups on the surface. This study also assessed the micro porosity of activated carbon with a mean pore diameter of 0.59 nm using a micropore size distribution curve activated carbons were conducted to Scanning Electron Microscopy (SEM).